Réponses

  • Utilisateur Brainly
2014-06-03T20:23:31+02:00
1 - 8/3 = 3/3 - 8/3 = - 5/3

8/3 - 1 = 8/3 - 3/3 = 5/3

8/5 - 1 = 8/5 - 5/5 = 3/5

3 - 1/4 = 12/4 = 1/4 = 11/4
Waow, ces super rapide, merci merci beaucoup
Je t'en prie ! :)
2014-06-03T20:24:35+02:00
1 - 8/3
= 1 x 3 / 1 x 3 - 8/3
= 3/3 - 8/3
= - 5/3

8/3 - 1
= 8/3 - 1 x 3 / 1 x 3
= 8/3 - 3/3
= 5/3

8/5 - 1
= 8/5 - 1 x 5 / 1 x 5
= 8/5 - 5/5
= 3/5

3 - 1/4
= 3 x 4 / 1 x 4 - 1/4
= 12/4 - 1/4
= 11/4
Merci beaucoup pour la réponse et la rapidité super génial
Avec plaisir :)